4. EFIKASI MENTIMUN (Cucumis sativus L.) TERHADAP PERCEPATAN PENYEMBUHAN LUKA BAKAR (Vulnus combustion) DERAJAT IIB PADA TIKUS PUTIH (Rattus norvegicus) (Efficacy of Cucumber (Cucumis sativus L.) on Healing of IIB Degree Burn Wound (Vulnus combustion) in Rat (Rattus norvegicus)) - Ummu Balqis (Universitas Syiah Kuala, 2016)
This research was aimed to determine the efficacy of cucumber (Cucumis sativus L.) on healing of burn wound IIB degree in rat (Rattus norvegicus). Experimental animal used were 6 male rats, aged 2-3 months with average weight of 150-250 grams. Rats were divided into 2 treatment groups, each group consist of 3 rats. Burn wound was made on the dorsal of the rats using a solder that has been linked with 2 cm diameter metal and heated for 5 minutes. The metal was placed for 5 seconds on each rat tail to form IIB degree burns. The burn wound were observed and treated according to the treatment group everyday. Group 1 as a negative control was smeared with aquades and group II was given the cucumber. Treatment of burn wound was conducted twice daily in the morning and evening until the diameter of the burn wound closed. Data were analyzed using independent t test. Statistical analysis showed that the healing of burn wound using a cucumber have no significant effect (P0.05) on reducing of burn wound diameter, red wound color and edema, scab formation and epithelization. This result can be concluded that the cucumber could not enhance the healing process of IIB degree wound burn on rats. ____________________________________________________________________________________________________________________ Key words: cucumber, burn wound, rat